Removal of acid blue 80 from aqueous solutions by adsorption on chemical modified bentonites. Issue 54 (19th November 2016) - Gomri, Fatima; Boutahala, Mokhtar; Zaghouane-Boudiaf, Hassina; Korili, Sophia A.; Gil, Antonio
Abstract: Batch sorption experiments were performed to study the adsorption of Acid Blue 80 (AB80) dye from aqueous solutions using chemical modified bentonites as adsorbents. A raw-bentonite (RB) was converted to sodium bentonite (NaB). The NaB was activated by acid leaching with sulfuric acid in order to obtain a sample (ANaB) with modified adsorption properties. The NaB and ANaB samples were exchanged with two alkyltrimethylammonium bromides (alkyl = C16 and C18) to evaluate the effect of the carbon chain length on the AB80 adsorption. The obtained samples were characterized by XRD, fourier transform infrared spectroscopy, nitrogen adsorption at −196°C, and through the determination of pHzpc . The effect of several operational parameters like pH, initial concentration of AB80, contact time, on the sorption behavior was studied. The adsorption kinetics were studied using pseudo-first-, pseudo-second-order and intraparticle diffusion models. The equilibrium adsorption data were analyzed using the Freundlich and Langmuir isotherm equation models. The Langmuir adsorption capacities ( q e ) were found to be 201, 179, 170, and 126 mg/g at 30°C respectively for ANaBC18, NaBC18, ANaBC16, and NaBC16.